Gut microbiota alterations in critically ill older patients: a multicenter study (2022)
ABSTRACT: Background: Aging generates changes in the gut microbiota, affecting its functionality. Little is known about gut microbiota in critically ill older adults. The objective of this study was to describe the profile of gut microbiota in a cohort of critically ill older adults. Methods: This observational study was conducted in five health institutions. Over a 6-month study period, critically ill patients over 18 years’ old who were admitted to the intensive care unit were enrolled. Fecal microbiota profiles were determined from 155 individuals, over 60 years old (n=72) and under 60 years old (n=83). Gut microbiota was analyzed by sequencing the V3-V4 region of the 16S rRNA gene. Alpha and beta diversity, operational taxonomic units and the interaction of gut microbiota with variables under study were analyzed. Amplicon sequence variants (ASVs) specifically associated with age were recovered by including gender, discharge condition, BMI, ICU stay and antibiotic ics as covariates in a linear mixed model. Results: In older adults, sepsis, malnutrition, antibiotic prescription and severity (APACHE and SOFA scores) were higher than in the group under 60 years of age. Alpha diversity showed lower gut microbiota diversity in those over 60 years of age (p<0.05); beta diversity evidenced significant differences between the groups (PERMANOVA=1.19, p= 0.038). The microbiota of the adults under 60 years old showed greater abundance of Murdochiella, Megasphaera, Peptoniphilus and Ezakiella, whereas those over 60 years old Escherichia-Shigella and Hungatella were more abundant. Conclusion: The gut microbial community was altered by different factors; however, age significantly explained the variability in critically ill patients. A lower presence of beneficial genera and a higher abundance of pathogens was observed in adults over 60 years old.